Implementation of artificial intelligence in the enterprise management system ("Journal "U". Economy. Management. Finance.", 2026)
The article examines the features of implementing artificial intelligence technologies in enterprise management systems. The main areas of artificial intelligence application, its impact on the effectiveness of managerial decision-making, as well as key risks and limitations of implementation are analyzed. The necessity of a comprehensive approach to the integration of intelligent technologies into enterprise activities is substantiated.
Keywords: artificial intelligence; enterprise management; digitalization; automation; business processes